2021
DOI: 10.1002/bab.2265
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted antiviral therapeutic potential of dietary flavonoids: Emerging trends and future perspectives

Abstract: Phytochemicals are the natural biomolecules produced by plants via primary or secondary metabolism, which have been known to have many potential health benefits to human beings. Flavonoids or phytoestrogens constitute a major group of such phytochemicals widely available in variety of vegetables, fruits, herbs, tea, and so forth, implicated in a variety of bio‐pharmacological and biochemical activities against diseases including bacterial, viral, cancer, inflammatory, and autoimmune disorders. More recently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 127 publications
(196 reference statements)
0
5
0
Order By: Relevance
“…The designed models were then refined using PROCHECK (Wiederstein and Sippl 2007), which revealed model 1 as the most stable structure with significant core residues (Figure 1A). Further, the complete quality examination by Z-score (-12.46) indicated that the obtained model was significantly close to the template (Sharma et al 2021c). As per the literature review, Histidine (HIS) at 123 positions, Lysine (LYS) at 125 positions, Glycine (GLY) at 127 positions, and Lysine (LYS) at 128 positions) formed the active site (Figure 1B) (Sharma et al 2020c).…”
Section: Methodsmentioning
confidence: 60%
“…The designed models were then refined using PROCHECK (Wiederstein and Sippl 2007), which revealed model 1 as the most stable structure with significant core residues (Figure 1A). Further, the complete quality examination by Z-score (-12.46) indicated that the obtained model was significantly close to the template (Sharma et al 2021c). As per the literature review, Histidine (HIS) at 123 positions, Lysine (LYS) at 125 positions, Glycine (GLY) at 127 positions, and Lysine (LYS) at 128 positions) formed the active site (Figure 1B) (Sharma et al 2020c).…”
Section: Methodsmentioning
confidence: 60%
“…Likewise, aging is also a progressive decline process with the accumulation of gene mutations and cellular-level epigenetic modifications, which may ultimately result in the development of aging-associated diseases including colon cancer (Zabransky et al 2022 ). Quercetin, a glycoside, has a high medicinal value, involved in a variety of cellular activities including anti-aging, cardiovascular, anti-inflammation, and anti-cancer activities (Salehi et al 2020 ; Sharma et al 2021 ). Hence, quercetin among the flavonoids is thought to have potential bioactivity as medicinal usage for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically, flavonoids are excellent antiviral and neuroprotective agents with proven therapeutic effects on various viral (deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) viruses) and neurological diseases [ 61 , 62 ]. Numerous preclinical studies have revealed the ability of flavonoids to affect several steps of the viral life cycle of different viruses, including herpesviruses [ 63 , 64 , 65 ]. The potent antiviral actions of flavonoids relate to the diversity of their chemical structures.…”
Section: Flavonoids: Chemical Background Antiviral and Neuroprotectiv...mentioning
confidence: 99%